Comparison between 200 ml and 1 liter packages of oral rehydration solution prepared by mothers of patients with diarrhea in the oral rehydration room - Muhammad Suryanto; Renny Hariati; Yati Soenarto; Moenginah P. A. (Indonesian Pediatric Society, 1988)
To have a comparison between the preparation of oral rehydration solution (ORS) of 200 ml and 1 liter packages, a study had been done in 30 mothers of children under five years of age suffering from diarrhea who treated their children in oral rehydration room (group I) and 30 mothers of non diarrheal children under five years sampled in the out-patient Department of Child Health, Dr. Sardjito General Hospital (group II). No significant difference was found (p <0.05) concerning the sodium concentration in th ORS of 200 ml and in the 1 liter package (group I: 85.95 ± 16.07, and 81.52 ± 16.21, group II 98.11 ± 24.67 and 97.02 ± 21.87) (mEq/L, Mean ± SD). Of 30 mothers group 11, 5 mothers (19.23%) made mistakes in preparing the I liter packages of ORS and the sodium concentration in this package was higher compared to the concentration in the 200 ml package. There was no significant difference concerning diluted volume and the sodium concentration between group I and the recommended method, but there was a significant difference (p < 0.005) between group II and recommended method. A significant difference was also found (p ( 0.001) between group I and group 11 about the mothers knowledge of the effect of diarrhea, the use of ORS, the amount of ORS that must be given lo !he patients and !he indications to refer the patients to !he health center or hospital.